Benefiting from basic education, school quality, and functional literacy in Kenya - Eisemon, Thomas Owen, 1943-1998 (Comparative and international education series, 1988)
Studies of the retention of literacy and numeracy by adults who have only obtained primary schooling have given little encouragement to the belief that the cognitive effects of schooling are enduring for many school leavers. How these findings can be reconciled with the claims made for the importance of schooling as an instrument of social and economic change is the subject ofinvestigation in this volume. The cognitive outcomes of literacy acqusition and secular schools in coastal Kenya are the focus of this ethnographic study, which stresses the relevance of an international understanding of the particular problems and dilemmas that face the educational systems of individual countries.